2003
DOI: 10.1007/bf03033758
|View full text |Cite
|
Sign up to set email alerts
|

Salvage chemotherapy with donor lymphocyte infusion and STI 571 in a patient relapsing with B-lymphoblastic phase chronic myeloid leukemia after allogeneic bone marrow transplantation

Abstract: Relapse is the main cause of treatment failure following hematopoietic stem cell transplantation for blastic phase chronic myeloid leukemia. Treatment options including donor lymphocyte infusion, second transplantation, interferon- and re-induction chemotherapy are often unsuccessful. We report a patient with blastic phase chronic myeloid leukemia relapsing after allogeneic stem cell transplantation. The post-transplant leukemia was characterized with B-lymphoid markers and multiple genetic abnormalities inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Patients who show the BCR/ABL rearrangement in progressively higher frequencies after the procedure are at greater risk of relapse and are candidates for additional and more aggressive therapies. However, patients with stable or decreasing frequencies seem to have immunological mechanisms suppressing the malignant clone, or perhaps this clone may lose its proliferative capacity resulting in a lower risk of relapse (Gopcsa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who show the BCR/ABL rearrangement in progressively higher frequencies after the procedure are at greater risk of relapse and are candidates for additional and more aggressive therapies. However, patients with stable or decreasing frequencies seem to have immunological mechanisms suppressing the malignant clone, or perhaps this clone may lose its proliferative capacity resulting in a lower risk of relapse (Gopcsa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2004) related a relapse rate at 2 years after the second allo-HSCT of 30%. The use of imatinib may also have a significant effect (Fujisawa et al, 2003;Gopcsa et al, 2003). Soydan et al (2005) concluded that imatinib treatment for molecular relapse after HSCT has an acceptable adverse event profile and provides a molecular remission rate of over 60%, but the response is short and 25% of the patients relapse again soon after drug cessation.…”
Section: Discussionmentioning
confidence: 99%